Analytical procedures for cadmium determination in facial make-up samples by graphite furnace AAS - Barros, Ariane Isis [UNESP]; Miranda, Kelber [UNESP]; Ferreira, Edilene Cristina [UNESP]; Neto, José Anchieta Gomes [UNESP] (My University, 2015)
This paper describes the development of analytical procedures for the determination of cadmium in facial make-up based on line-source graphite furnace AAS (LS-GFAAS) and direct solid sampling (DSS) coupled to a high-resolution continuum source graphite furnace AAS (HR-CS-GFAAS). Eye shadow, blush, and compact powder samples were analyzed by LS-GFAAS after microwave-assisted digestion with an HNO3/H2O2/HF mixture. Use of boric acid to eliminate HF from the digests was not feasible due to precipitation. Ammonium hydroxide was then dispensed into the graphite platform to eliminate HF and reduce digest acidity. The DSS HR-CS GFAAS procedure did not require any previous treatment. Both proposed procedures were validated using a certified reference material. Then, cadmium was determined in six facial make-up samples by LS-GFAAS and DSS HR-CS GFAAS with calibration against aqueous standard solutions. A paired Mest at a 95% confidence level showed that the DSS HR-CS GFAAS procedure enabled the achievement of similar results as those obtained by LS-GFAAS after acid digestion. The precision, expressed as the relative standard deviation, varied from 2.0 to 9.1% (LS-GFAAS) and from 1.0 to 11.1% (DSS HR-CS GFAAS). The DSS HR-CS GFAAS procedure was then applied for the determination of cadmium in 30 blush samples and 130 eye shadow samples of different brands and colors. The cadmium concentration varied from 12 to 111 ug kg-1 in the blush samples and from 5.1 to 198 ug kg-1 in the eye shadow samples.